Subsidies are Potential Sources of Profitable Management – Their Payment Between 2010 and 2016 - Jávor, Bence; Nábrádi, András; Kukovics, Sándor (Applied Studies in Agribusiness and Commerce, 2018)
Based on the allocations and distributions of subsidies in the sheep sector in the previous years (2004-2009), the authors examined the sum of aids claimed and paid from 2010 to 2016 and their farm-size related changes. The following data were collected from the Agricultural and Rural Development Institute on payments under specific subsidy titles, classified by sheep and goat farm sizes: 0-50; 51-100, 101-200, 201-300 and also 0-100, 101-300, 301-500, 501-1000, 1001-5000 and above 5000. Data procession was carried out by the SPSS for Windows 22 program. The size and population of the examined sheep sector underwent visible changes during the studied years leading to a reduction rather than growth. Their analysis highlights that size distribution of sheep farms has changed significantly in recent years, combined with simultaneous modifications of their sheep stock sizes in production. Their conclusions suggest that effects of years and farm sizes in the sheep and goat sector have considerably modified the aid sums paid under different titles. JEL Classification: H5, Q14